Experience of using a fixed-dose combination of perindopril and amlodipine in the clinical practice settings: a real-world opportunity to increase antihypertensive therapy effectiveness - O. D. Ostroumova; T. F. Guseva; O. V. Bondarets (Российский кардиологический журнал)
The paper presents the results of the studies on effectiveness and safety of a fixeddose combination of perindopril A and amlodipine (Prestans) in the real-world clinical practice settings in Russia and other countries. The focus is on the evidence of fast and strong antihypertensive action of this medication, its excellent tolerability, and increased therapy compliance. The evidence presented justifies a wider use of this fixed-dose combination of perindopril A and amlodipine in order to improve blood pressure control in hypertensive patients.